Sagot :
Bonjour,
Développer l'expression :
C = (3y + 4)² + (4y + 1)(2y - 4)
→ identité remarquable :
- (a + b)² = a² + 2ab + b²
C = (3y)² + 2*3y*4 + 4² + (4y + 1)(2y - 4)
C = 9y² + 24y + 16 + (4y + 1)(2y - 4)
C = 9y² + 24y + 16 + 8y² - 16y + 2y - 4
C = 9y² + 24y + 16 + 8y² - 14y - 4
C = 9y² + 8y² + 24y - 14y + 16 - 4
C = 17y² + 10y + 12
- Coefficient placé devant le y² : 17
Factoriser l'expression :
D = (2x + 3)(3x - 2) - (2x + 3)²
D = (2x + 3)(3x - 2) - (2x + 3)(2x + 3)
D = (2x + 3)(3x - 2 - (2x + 3))
D = (2x + 3)(3x - 2 - 2x - 3)
D = (2x + 3)(x - 5)
- Coefficients placés devant les x : 2 et 1
Bonne journée.